2018
DOI: 10.3390/jmmp2020022
|View full text |Cite
|
Sign up to set email alerts
|

Coating of Ultra-Small Micro End Mills: Analysis of Performance and Suitability of Eight Different Hard-Coatings

Abstract: Due to the constant need for better functionalized surfaces or smaller, function integrated components, precise and efficient manufacturing processes have to be established. Micro milling with micro end mills is one of the most promising processes for this task as it combines a high geometric flexibility in a wide range of machinable materials with low set-up costs. A downside of this process is the wear of the micro end mills. Due to size effects and the relatively low cutting speed, the cutting edge is espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Such cumulative cycles negatively affect several important parameters at the same time, such as surface roughness, burr formation, maximal achievable quality, and finally, production time and costs. As consequence, the level of tool wear plays a major role for predicting the tool-life [8].…”
Section: Tool-life Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Such cumulative cycles negatively affect several important parameters at the same time, such as surface roughness, burr formation, maximal achievable quality, and finally, production time and costs. As consequence, the level of tool wear plays a major role for predicting the tool-life [8].…”
Section: Tool-life Capabilitymentioning
confidence: 99%
“…The tool is therefore expected to withstand the conditions imposed by the milling process for a longer period of time. Reichenbach et al [16], Uhlmann et al [17], and Bohley et al [8] reported promising results using micro tools coated with TiN (titanium nitride), diamond, and TiB 2 (titanium diboride), respectively. However, the use of coatings for micro tools D ≤ 50 μm has the disadvantage of increasing the cutting-edge radius expressively, which in turn leads to higher process forces and lower cutting capabilities.…”
Section: Wear Of Micro-end Millsmentioning
confidence: 99%
“…As a consequence, measurements of the micro hardness on rough surfaces are not comparable. At the same time, the measurement of micro hardness on a known or unknown microtopography may be of particular interest in individual cases, like heat-treated materials, thin coated materials, work hardened surfaces, or microstructured surfaces, whose microtopography is of functional relevance [14]. If such components were polished (removal of microtopography), the characteristic to be examined would be lost.…”
Section: Introductionmentioning
confidence: 99%